Is the value worth the costs?: Examining the experiences of preservice teachers of color in predominantly White colleges of education. Issue 1 (2nd January 2022) - Archer, Amerah; Kumar, Revathy; Pilcher, Eric
ABSTRACT: Recruiting and retaining students of color in colleges of education in predominately White institutions (PWIs) is a source of concern. Efforts to reverse this trend have proven unsuccessful. This article uses the Expectancy-Value-Cost motivational framework to understand three underlying cultural costs that negatively impact preservice teachers of color, namely cultural dissonance, belonging uncertainty and stereotype threat. We propose that ameliorating cultural costs for preservice teachers of color enhances their expectations for successful graduation and increases the subjective value of the teaching profession. Finally, we discuss practices that can be implemented at the interpersonal, instructional, and institutional organizational levels to ameliorate these cultural costs.